2020
DOI: 10.2337/dc20-1531
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Impact of Real-time Continuous Glucose Monitoring in Adults With Type 1 Diabetes on Insulin Pump Therapy: Results After the 24-Month RESCUE Study

Abstract: OBJECTIVE In recent years, a growing number of people with type 1 diabetes gained access to real-time continuous glucose monitoring (rtCGM). Long-term benefits of rtCGM are unclear because of a lack of large studies of long duration. We evaluated whether real-world rtCGM use up to 24 months offered benefits, particularly in those living with impaired awareness of hypoglycemia (IAH). RESEARCH DESIGN AND METHODS This 24-month, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
(26 reference statements)
0
31
0
1
Order By: Relevance
“…CGM systems provide a comprehensive view of glucose profiles identifying patterns, areas of glucose variability (GV), and time spent in, below, or above range (time in range [TIR]: 70‐180 mg/dL [3.9‐10.0 mmol/L]), thereby allowing patients to make therapeutic adjustments to improve metabolic control. The use of CGM systems has been shown to positively impact the management of PWD1 with the potential to lower HbA1c, enhance time spent in range, reduce the frequency of and time spent in hypoglycaemia and hyperglycaemia, lower glycaemia variability, and improve QOL 2,3,7‐15 . With the use of CGM, an International Consensus on TIR was published in 2019 with the recommendation to spend more than 70% TIR, a percentage that has a strong association with an HbA1c level of 7.0% (53 mmol/mol) 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…CGM systems provide a comprehensive view of glucose profiles identifying patterns, areas of glucose variability (GV), and time spent in, below, or above range (time in range [TIR]: 70‐180 mg/dL [3.9‐10.0 mmol/L]), thereby allowing patients to make therapeutic adjustments to improve metabolic control. The use of CGM systems has been shown to positively impact the management of PWD1 with the potential to lower HbA1c, enhance time spent in range, reduce the frequency of and time spent in hypoglycaemia and hyperglycaemia, lower glycaemia variability, and improve QOL 2,3,7‐15 . With the use of CGM, an International Consensus on TIR was published in 2019 with the recommendation to spend more than 70% TIR, a percentage that has a strong association with an HbA1c level of 7.0% (53 mmol/mol) 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Following the success of the Belgian CGM-CSII realworld study (29) and its continuation-the RESCUE trial (30), where, similarly to the previously discussed SILVER study, a sustained benefit of real-time CGM is demonstrated over 24 months-this FUTURE trial shows the efficacy of isCGM along with higher treatment satisfaction, less severe hypoglycemia, and consequently less hospital admission and less work absenteeism over 12 months, with immediate direct and indirect savings to the national health insurance. The number of sensor scans per day was significantly associated with the decrease in A1c.…”
Section: Commentmentioning
confidence: 70%
“…84 Similar findings were reported in the RESCUE trial, another prospective, observational study that demonstrated significant reductions in hospitalizations for severe hypoglycemia (from 11.9% to 3.17%) and DKA (4.6% to 1.06%) following 12 months of rtCGM use in conjunction with insulin pump therapy. 85 Using evidence from an earlier RCT of adults with T2D treated with non-intensive insulin therapy, 86 investigators of a 2016 costeffectiveness modeling study assessed the projected lifetime clinical and economic outcomes of rtCGM use and determined that intermittent, short-term use of rtCGM is both clinically effective and a cost-effective disease management adjunct in this population. 66 Insulin Delivery Technologies Insulin Pumps.…”
Section: Continuous Glucose Monitoring Technologiesmentioning
confidence: 99%
“…11,83,146e155 Studies have also shown significant reductions in hospitalizations for acute diabetes-related events and absenteeism. 85,156,157 The large, randomized, 24-week DIAMOND trial demonstrated that the use of rtCGM in persons with T1D treated with MDI compared with SMBG resulted in lower A1C levels (-1.0% vs 0.4%, P < .001), with significant reductions in time spent at <70 mg/dL (-22 vs 37 min/d, mean difference 59 min/d, P ¼ .002) and >250 mg/ dL (-78 vs 78 min/d, mean difference 156 min/d, P < .001). 83 Significant reductions in diabetes-related distress and greater hypoglycemic confidence among the rtCGM users were also reported.…”
Section: Evidence Basementioning
confidence: 99%